Study on seismic behavior of a self-centering railway bridge pier with sacrificial components. (January 2022) - Xu, Feng; Zhang, Xiyin; Xia, Xiushen; Shi, Jun
Abstract: Railway bridge pier with large cross-section will vibrate significantly during strong earthquake events. Sacrificial components can be used to improve the lateral stiffness and control the initial uplift of the self-centering pier during earthquakes. This study investigated the seismic isolation mechanism and behavior of a self-centering railway bridge pier with sacrificial components by experimental and numerical methods. Based on an actual railway bridge, a 1/30 scaled bridge pier model was designed for pseudo-static test. Constant axial load and cyclic lateral load were applied for the scaled bridge pier model. Test results showed that sacrificial components were fractured when the loading displacement exceeded 25 mm. The hysteretic behaviors of the self-centering pier exhibited significant difference before and after the failure of sacrificial components. It was found that the bridge pier concrete cracked but steel bars did not yield during the test. This indicated that the failure of sacrificial components of the self-centering bridge pier can effectively protect the pier from severe damage during earthquakes. Furthermore, a Four-spring model was proposed with assistance of the Opensees software platform, and it was verified by pseudo-static test results. It is demonstrated that the proposed model can simulate the self-centering piers with sacrificial components under cyclic lateral loading.